Redox and proteolytic regulation of cardiomyocyte β1-adrenergic receptors – a novel paradigm for the regulation of catecholamine responsiveness in the heart - Steinberg, Susan F. (Frontiers in Immunology, 2023)
Conventional models view β1-adrenergic receptors (β1ARs) as full-length proteins that activate signaling pathways that influence contractile function and ventricular remodeling -and are susceptible to agonist-dependent desensitization. This perspective summarizes recent studies from my laboratory showing that post-translational processing of the β1-adrenergic receptor N-terminus results in the accumulation of both full-length and N-terminally truncated forms of the β1AR that differ in their signaling properties. We also implicate oxidative stress and β1AR cleavage by elastase as two novel mechanisms that would (in the setting of cardiac injury or inflammation) lead to altered or decreased β1AR responsiveness.